Enhancing Port Security and Predictive Maintenance with IoT: Cadets' Perspectives - Susi Herawati; Rosna Yuherlina Siahaan; April Gunawan Malau; Derma Watty Sihombing; Boedojo Wiwoho Soetatmoko Jogo; Ronald Simanjuntak (LPPM POLITEKNIK LP3I BANDUNG, 2024)
This research explores the perspectives of 100 cadets studying multimodal transportation on integrating Internet of Things (IoT) to enhance port security and predictive maintenance. Using qualitative methods, including interviews and document analysis, the study investigates the effectiveness of IoT in real-time monitoring, data security, and predictive maintenance. The findings highlight cadets' recognition of IoT's potential to transform port operations, particularly in improving security measures and maintenance strategies. Cadets also emphasize the importance of professionalism and adherence to standards in IoT integration, valuing compliance with standards, understanding of IoT, training and education, and ethical considerations. The research underscores the need for continuous education and training programmes to prepare future industry professionals for the challenges and opportunities presented by IoT technologies. Overall, this study contributes to the advancement of knowledge in transportation management and education, offering insights for policymakers, industry practitioners, and educators on the integration of IoT in port operations.